2017
DOI: 10.5194/amt-10-2105-2017
|View full text |Cite
|
Sign up to set email alerts
|

Differences in liquid cloud droplet effective radius and number concentration estimates between MODIS collections 5.1 and 6 over global oceans

Abstract: Abstract. Differences in cloud droplet effective radius and cloud droplet number concentration (CDNC) estimates inferred from the Aqua-MODIS (Moderate Resolution Imaging Spectroradiometer) collections 5.1 (C5.1) and 6 (C6) cloud products (MYD06) are examined for warm clouds over global oceans for the year 2008. Individual pixel level retrievals for both collections are aggregated to 1 • × 1 • and compared globally and regionally for the three main spectral channel pairs used for MODIS cloud optical property re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…In agreement with the results found by Rausch et al (), N d tends to have lower values across the tropics and subtropics in C6 data compared to C5 (using the 3.7‐μm retrieved r e in both cases). In Rausch et al () N d differences were attributed to the corrections to the band‐averaged solar irradiances, atmospheric emission factors, and changes in cloud top pressure as used in the new C6 look up tables. On average, the root mean square differences among the three data sets examined are approximately within 20 cm −3 or ±20%.…”
Section: Current Nd Data Sets and Intercomparisonssupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with the results found by Rausch et al (), N d tends to have lower values across the tropics and subtropics in C6 data compared to C5 (using the 3.7‐μm retrieved r e in both cases). In Rausch et al () N d differences were attributed to the corrections to the band‐averaged solar irradiances, atmospheric emission factors, and changes in cloud top pressure as used in the new C6 look up tables. On average, the root mean square differences among the three data sets examined are approximately within 20 cm −3 or ±20%.…”
Section: Current Nd Data Sets and Intercomparisonssupporting
confidence: 91%
“…Other improvements to the handling of the surface reflectance in Collection 6 (see Platnick et al, ) include a new surface spectral albedo data set derived from dynamic 8‐day sampling of MODIS data (previously Collection 5 used a 5‐year surface albedo climatology, see Platnick et al, ) and the inclusion of land spectral emissivities that are consistent with the cloud top property algorithm. Rausch et al () showed that for one MODIS ocean scene Collection 6 r e was up to 1 μm lower than that from Collection 5 for optically thin ( τc 2–3) clouds, which may be due to the surface albedo, although other changes between Collections 5 and 6 have also been made. However, Zhang and Platnick () found little effect upon r e3.7 versus r e2.1 differences from the implementation of the Cox and Munk () scheme for global marine liquid clouds.…”
Section: Retrieval Of Nd From Passive Satellite Observationsmentioning
confidence: 99%
“…These improvements include a better coregistration of the visible and near-infrared focal planes of the Aqua-MODIS instrument as well as significant improvements in the forward radiative transfer models used in the retrieval framework (Platnick et al, 2015). The impact of these changes on CDNC retrievals and gridded climatologies is assessed in detail in Rausch et al (2017). For the current study, Level-2 cloud retrievals are from Aqua-MODIS spanning the years 2003 through 2015.…”
Section: Modis Collection 6 Cloud Parametersmentioning
confidence: 99%
“…Figure 3a shows the effective radius of the cloud droplets in the top layer of stratiform clouds without ice in the default PD-simulation, while Figure 3b shows the difference in the effective radius between PI and PD. The effective radius of cloud droplets in CAM5.3-Oslo is slightly lower than that of MODIS (Moderate Resolution Imaging Spectroradiometer) (Rausch et al, 2017), which we find acceptable due to the positive biases associated with the r e -products coming from MODIS (Liang et al, 2015;Painemal & Zuidema, 2011). Changes in r e between PI and PD are mostly negative, owing to the Twomey effect when aerosol concentrations increase.…”
Section: Size-dependent Evaporationmentioning
confidence: 63%